Right Ventricular Myocardial Infarction : Presentation and Acute Outcomes (TAJ: Journal of Teachers Association, 2018)
Right Ventricular Infarction (RVI) complicating inferior wall myocardial infarction (MI) is common and associated with significant morbidity and mortality. We try to systematically assess the incidence, clinical presentation and in hospital outcomes of right ventricular myocardial infarction in a tertiary-care set up. This study was a descriptive, cross sectional observational series of consecutive patients with RVMI. All patients with acute inferior myocardial infarction (n=100) were enlisted. RVMI was diagnosed by ≥1mm ST elevation in lead V4R in right sided electrocardiogram. RVI occurred in 31% (n=31) of patients of acute inferior infarctions. Patients with isolated inferior myocardial infarction served as controls (n=69). Echocardiography was performed within 24 hours of admission. From both groups, 51% were qualified for thrombolysis. The incidence of hypotension (96.7%), cardiogenic shock (64.5%), bradycardia and heart block were much higher in RVI than in inferior myocardial infarction. Clinically manifest RV dysfunction (raised jugular venous pulse, hypotension and tricuspid regurgitation) and right ventricular dilatation detected by echocardiography was seen in a variable number of patients. In hospital mortality rate was significantly higher (n=13, 41.9%) in right ventricular infarction group than in inferior myocardial infarction group (n=2, 2.9%)TAJ 2012; 25: 42-46